The Investigatory Powers Act 2016 and Connected Vehicles: A New Form of Panspectric Veillance Looming?. (26th April 2022) - Marson, James; White, Matthew; Ferris, Katy
Abstract: Connected and autonomous vehicles (CAVs) currently exist in varying states of readiness to, at one end of the spectrum, assist the driver in normal driving activities and at the other operate in fully autonomous mode, requiring no driver input at all. In facilitating these features, CAVs create, give access to, and allow communication of the data produced. The further along the autonomous scale CAVs progress, the greater the data generated, which are being harvested by original equipment manufacturers (OEMs), often unwittingly by the end user. The operation of the Investigatory Powers Act 2016 gives government agencies power to compel the retention and access to these data. Here we argue that the definitions within the Act result in CAV OEMs being subject to retention notices of the data generated by these vehicles. This issue, its extent and potential for abuse, and the lack of protection for those associated with the use of CAVs, hitherto unexamined in the legal academic literature, is the focus of this paper.